Does Fake News Matter to Election Outcomes?: The Case Study of Taiwan’s 2018 Local Elections - Tai-Li Wang (Asian Journal for Public Opinion Research)
Fake news and disinformation provoked heated arguments during Taiwan’s 2018 local election. Most significantly, concerns grew that Beijing was attempting to sway the island’s politics armed with a new “Russian-style influence campaign” weapon (Horton, 2018). To investigate the speculated effects of the “onslaught of misinformation,” an online survey with 1068 randomly selected voters was conducted immediately after the election.